Quantitative magnetic resonance (MR) neurography for evaluation of peripheral nerves and plexus injuries - Martín Noguerol, Teodoro (Quant Imaging Med Surg, 2017)
Traumatic conditions of peripheral nerves and plexus have been classically evaluated by morphological imaging techniques and electrophysiological tests. New magnetic resonance imaging (MRI) studies based on 3D fat-suppressed techniques are providing high accuracy for peripheral nerve injury evaluation from a qualitative point of view. However, these techniques do not provide quantitative information. Diffusion weighted imaging (DWI) and diffusion tensor imaging (DTI) are functional MRI techniques that are able to evaluate and quantify the movement of water molecules within different biological structures. These techniques have been successfully applied in other anatomical areas, especially in the assessment of central nervous system, and now are being imported, with promising results for peripheral nerve and plexus evaluation. DWI and DTI allow performing a qualitative and quantitative peripheral nerve analysis, providing valuable pathophysiological information about functional integrity of these structures. In the field of trauma and peripheral nerve or plexus injury, several derived parameters from DWI and DTI studies such as apparent diffusion coefficient (ADC) or fractional anisotropy (FA) among others, can be used as potential biomarkers of neural damage providing information about fiber organization, axonal flow or myelin integrity. A proper knowledge of physical basis of these techniques and their limitations is important for an optimal interpretation of the imaging findings and derived data. In this paper, a comprehensive review of the potential applications of DWI and DTI neurographic studies is performed with a focus on traumatic conditions, including main nerve entrapment syndromes in both peripheral nerves and brachial or lumbar plexus.